Character Association and Path Analysis under Stress and Non-stress Conditions in Pearl Millet - Manga, V K (Annals of Arid Zone, 2016)
Correlation and path coefficient analyses were carried out in 58 genotypes of pearl millet under stress (rainfed) and non-stress (irrigated) conditions. Under non-stress condition grain yield pet plot was associated positively and significantly with plant height, productive tillers per plant and grain yield per plant, and negatively with days to 50% flowering. Under stress conditions grain yield per plot was associated positively with early vigor in addition to above traits. Path coefficients analysis revealed that under non-stress condition, grain yield per plant and plant height had higher positive direct influence on grain yield per plot, while 50% flowering had high negative direct effect on grain yield per plot. Productive tillers per plant had the highest positive direct efIect on grain yield per plant. Under stress condition, grain yield per plant, plant height and early vigor had positive direct effect’ on grain yield per plot, while productive tillers per plant and early vigor directly influenced grain yield per plant. Thus, for improving grain yield of pearl millet under stress environments, besides productive tillers per plant, plant height and earliness, emphasis should also be given to early vigorous growth